Analisis tegangan pada struktur mesin pencacah plastik menggunakan metode elemen hingga (MEH) dan uji kerja mesin pencacah plastik - Hendra Hendra; A. Indriani; Hernadewita Hernadewita; A. Mardian; N. Kholik; Rispandi Rispandi; Y. Suhartini (METAL: Jurnal Sistem Mekanik dan Termal, 2021)
Plastic is a non-biodegradable material. Plastic waste must be processed using processing machines or other processing methods such as processing plastic into fuel and other forms of products. Plastic waste processing machines are available in plastic shredding and injection machines. The performance of plastic shredding and injection machines depends on the plastic waste treated, the shape of the cutting edge, the structural strength of the plastic shredding and injection machines and others. The strength of plastic shredding and injection machines can be calculated by means of simulation using the finite element method (FEM). This method will save costs, selection of materials and cutting edge shapes quickly and easily and soon. In this study, FEM was used to simulate the design strength of a plastic shredding and injection machines in the form of pressure and displacement, followed by the manufacture of plastic shredding and injection machines and the work test of plastic shredding and injection machines. From the simulation results using FEM, the maximum voltage and structural displacement of plastic cutting and injection machine is 4.57 MPa and 0.031 mm and work test showed the machine can cut 800 grams of plastic waste in 278 seconds with motor rotation of 176 rpm, current 6.8 A, active force. Electrical load 1214.4 watts and torque 44.74 lb.ft.